2001
DOI: 10.1211/0022357011775875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steroidal and non-steroidal antiphlogistic drugs on eicosanoid synthesis in irritated skin: studies with the isolated perfused bovine udder

Abstract: Using the isolated perfused bovine udder as an in-vitro model of skin inflammation, the effects of topically administered arachidonic acid on prostaglandin and leukotriene synthesis have been shown previously. In this study, the effects of indometacin (indomethacin) and clobetasol-17-propionate (administered topically) as well as flunixin meglumine and meloxicam (administered via the perfusion fluid) have been studied. Compared with controls, arachidonic acid caused a significant increase in the dermal prostag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Steps were therefore taken to minimise this (immediate flushing with well‐gassed Tyrode solution in the abattoir; minimal delay in setting up) and vascular endothelial function was also confirmed in the laboratory. The isolated, perfused udder preparation has been used to study mammary metabolism (Wood et al 1965; Hardwick, 1966), the mechanisms of milk production (Hardwick & Linzell, 1960) and the pharmacology (Kietzmann et al 1993) and pathophysiology (Bäumer & Kietzmann, 2001) of the skin. The present study shows that the isolated perfused udder is also a useful model for the study of local mediator release and modulation of mammary blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steps were therefore taken to minimise this (immediate flushing with well‐gassed Tyrode solution in the abattoir; minimal delay in setting up) and vascular endothelial function was also confirmed in the laboratory. The isolated, perfused udder preparation has been used to study mammary metabolism (Wood et al 1965; Hardwick, 1966), the mechanisms of milk production (Hardwick & Linzell, 1960) and the pharmacology (Kietzmann et al 1993) and pathophysiology (Bäumer & Kietzmann, 2001) of the skin. The present study shows that the isolated perfused udder is also a useful model for the study of local mediator release and modulation of mammary blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the isolated bovine udder perfused with Tyrode solution has been used in a series of studies by Kietzmann and his colleagues (e.g. Kietzmann et al 1993; Bäumer & Kietzmann, 2001) as an elegant model to study the cutaneous absorption of topical drugs. The model of Kietzmann and his colleagues was used as a starting point for the model described in the present paper.…”
mentioning
confidence: 99%
“…The collection of different parameters (glucose consumption, lactate production, lactate dehydrogenase activity, and pH in the perfusate, histological examination) indicated that skin viability was retained during a six hour perfusion interval and determination of udder skin-fold thickness demonstrated that no edema developed (Kietzmann et al, 1993). Subsequently, different anti-inflammatory drugs, administered systemically via the perfusate or topically to the skin, were tested in the model for their effect on eicosanoid synthesis (Bäumer and Kietzmann, 2001). The perfusion model also served as the basis for studies on the transdermal absorption potential of vitamin E acetate from cosmetic formulations (Lampen et al, 2003).…”
Section: Livermentioning
confidence: 99%
“…The validation of new methods is of great interest. One of these new methods, the isolated perfused bovine udder approach, has been used in studies of mammary gland metabolism (Massart-Leën et al, 1986;Ehinger et al, 2006) and cutaneous absorption of drugs and cosmetics (Bäumer and Kietzmann, 2001). Despite of its potential, the method has not been widely used to evaluate the response against pathogens.…”
Section: Introductionmentioning
confidence: 99%